2006
DOI: 10.1038/sj.bjp.0706852
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptor‐activated cationic channels in murine ileal myocytes

Abstract: Background and purpose: There is little information about the excitatory cholinergic mechanisms of mouse small intestine although this model is important for gene knock-out studies. Experimental approach: Using patch-clamp techniques, voltage-dependent and pharmacological properties of carbacholor intracellular GTPgS-activated cationic channels in mouse ileal myocytes were investigated. Key results: Three types of cation channels were identified in outside-out patches (17, 70 and 140 pS). The voltage-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…28) Lee et al 3) suggested that TRPC5 was a promising candidate for muscarinic cationic channel in murine gastric myocytes. As the properties of I CCh in murine ileal myocytes are consistent with a previous report about nonselective cation channels activated by muscarinic stimulation in murine gastric myocytes, 30) TRPC5 may also be a promising candidate for muscarinic cationic channel in murine ileal myocytes. The effect of CaM and MLCK on murine ileal myocytes was similar to that of TRPC5, suggesting TRPC5 to be a candidate for NSCC, activated by muscarinic stimulation.…”
Section: Discussionsupporting
confidence: 76%
“…28) Lee et al 3) suggested that TRPC5 was a promising candidate for muscarinic cationic channel in murine gastric myocytes. As the properties of I CCh in murine ileal myocytes are consistent with a previous report about nonselective cation channels activated by muscarinic stimulation in murine gastric myocytes, 30) TRPC5 may also be a promising candidate for muscarinic cationic channel in murine ileal myocytes. The effect of CaM and MLCK on murine ileal myocytes was similar to that of TRPC5, suggesting TRPC5 to be a candidate for NSCC, activated by muscarinic stimulation.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, we hypothesized that Rho-kinase may regulate NSCC involved in depolarization responses to cholinergic stimulation. Dialysis with GTPgS stimulates CCh-like NSCC through activation of multiple G proteins (Helliwell and Large, 1997;Dresviannikov et al, 2006). In the present study, currents activated by GTPgS currents were inhibited by Y-27632, suggesting that decreased depolarization by CCh in the presence of Y-27632 could be due to inhibition of NSCC.…”
Section: Figurementioning
confidence: 48%
“…When measured with Ca 2+ buffered to about 0.1 mM, the muscarinic agonist, carbachol, elicited a robust I cat that exhibited the typical U-shape dependence on membrane voltage (Dresviannikov et al 2006;Sakamoto et al 2006). The response in smooth muscle cells from either M 2 or M 3 KO mice was greatly attenuated (Sakamoto et al 2007).…”
Section: Nonselective Cation Conductancementioning
confidence: 94%